The Influence of the Muhaddisat's Profession on the Matan Hadiths They Reported in Kutub al-Tis'ah - Suci Amalia Yasti; Alfiah Rafika; Doni Saputra (Al-Shamela : Journal of Quranic and Hadith Studies, 2024)
Muhaddisat are female hadith narrators who are rarely discussed, even though they also narrate many traditions. For example, Aisha RA is the fourth most narrated hadith with 2210 traditions. Many of the traditions narrated by muhaddisat relate to things that only women experience and are related to their daily activities. This article aims to determine the influence of the traditions narrated by the muhaddisat on her profession. The author uses a qualitative method by investigating the traditions narrated by the muhaddisat in the books of hadith by clarifying them based on their professions. The hadith data is then investigated in the kutub al-tis’ah which contains seven professions of muhaddisat using the keyword profession. The data that the author found that the muhaddisat had seven professions related to their narrations, namely, Saudah bint Zam'ah as an animal tanner has 3 traditions in which the text of the tradition discusses tanning animals, Asma' bint Abu Bakr as a farmer and gardener has 2 traditions in which the text of the narrated tradition discusses her profession, Asma' bint Yazid as a bridal dresser has 1 tradition in which the text of the tradition is about her profession as a bridal dresser, Shifa' bint 'Abd Allah ibn 'Abd Shamsy as a teacher and cupping expert has 1 hadith in which the text is about her profession, Salma as a medic and midwife has 1 hadith in which the text is about her profession, Umm Aiman and Umm 'Ayyasy as servants have 1 hadith in which the text is about her profession as a servant, and Lubabah as the caretaker of the Prophet's grandson who has 1 hadith in which the text is about how he took care of the grandson of the Prophet. Based on these data, it can be concluded that the profession of the muhaddisat has an influence on the hadith that they narrate so that the text discusses their profession.